Modes of Extraction in Latin America's Lithium Triangle: Explaining Negotiated, Unnegotiated, and Aborted Mining Projects. (23rd February 2023) - González, Lucas I.; Snyder, Richard
ABSTRACT: Mitigating climate change requires a global transition from fossil fuels to a "green economy" driven by renewable energies. This shift has fostered massive investments in mining resources, notably lithium in South America, needed to store renewable energies. These mining ventures often produce harmful externalities where lithium is located. In Argentina, a major producer, striking variation has occurred in the fortunes of lithium-mining projects. In some instances, mining companies offered concessions that mitigated environmental damage and improved local socioeconomic conditions. In others, companies made minimal concessions, and in a third set they halted projects in response to local resistance. Why do mining ventures result alternatively in negotiated, unnegotiated, or aborted extraction? The article proposes a new typology of modes of extraction together with a multilevel explanatory framework that centers on the strengths and strategies of transnational mining companies, subnational governments, and local communities in setting the terms for extracting lithium.